Migration of a fractured ring IUD resulting in vesicovaginal fistula and vaginal calculus. (3rd September 2018) - Yan, Dewen; Shi, Zhan; Wang, Liping; Zhao, Xiumin
Abstract: Case: Although many complications have been reported with intrauterine contraceptive devices (IUDs), vesicovaginal fistula with secondary vaginal stones is rare. We report the case of a 46-year-old woman who presented with a vaginal discharge lasting 2 months. Two years previously, she had undergone cystoscopic lithotripsy and surgery to remove an IUD, after pelvic radiography had revealed a fractured Chinese stainless steel ring IUD with secondary vesical stones that had been the cause of her urinary tract symptoms. When she again complained of vaginal discharge, vaginal stones and a vesicovaginal fistula were found on physical examination and CT urography. The patient underwent stone removal and concurrent vesicovaginal fistula repair. IUD fragments were found in the vesicovaginal and rectovaginal spaces. No abnormalities were found at follow-up 6 months after surgery. Conclusion: In any woman undergoing surgery to remove a migrated IUD, complete exposure and removal of the IUD are necessary to avoid fracturing of the IUD, secondary breakage and residue.